Implementasi Merdeka Belajar Dalam Pembelajaran Pendidikan Agama Islam Pada Pendidikan Dasar - Wahidah, Evita Yuliatul; Sulaeman, Radzie (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
The evolution of education in Indonesia is closely tied to curriculum reforms, which undergo evaluations at specific intervals. There is a common perception that curriculum changes occur with shifts in policy leadership. Currently, the new curriculum introduced is the "Kurikulum Merdeka," or Independent Curriculum. This curriculum is designed to provide a learning environment where students can learn calmly, comfortably, enjoyably, and without stress or pressure, allowing them to showcase their natural talents. This research aims to explore and analyze the "Implementation of Independent Learning in Islamic Religious Education (PAI) at Elementary Schools (A Case Study at SDN 4 Cisarua Samarang Garut)." The study employs a qualitative approach with a case study method. The descriptive qualitative research method is used to describe, uncover, explain, and analyze the phenomena, events, and activities related to the implementation of independent learning in PAI at SDN 4 Cisarua Samarang Garut. The goal is to enhance the quality and outcomes of learning for elementary students. Based on the research findings, it can be concluded that the implementation of Independent Learning in PAI at the elementary education level has successfully achieved the desired outcomes. Although there is room for improvement, particularly in the utilization of technology, it is evident that this approach has positively impacted the quality of learning, created a conducive learning environment, and increased the focus on students as active learners. Keywords : Implementation of Independent Learning, Islamic Religious Education, Elementary Education